The application of system dynamics to resource allocation in international NGOs: exploring and modelling power inequalities whilst increasing efficiencies in complex international NGO management systems - Fourie, Tamryn-Lee (Department of Statistical Sciences, 2019)
We are living in an unjust world where the majority of humanity is subject to unequal economic and public policy systems that perpetuate cycles of poverty. Civil society, of which international NGOs are major players, are acknowledging the need for systemic, transformational change, which has to include meaningful participation in decision making processes by those whom are most vulnerable. In order to more effectively play this role, a number of international NGOs are moving decentralised structures (often comprised of independent entities at country level) to legitimately represent their primary constituents - those that are vulnerable, living in poverty, mostly in the global South. A consequence of this trajectory is added internal complexity and the creation of new management challenges, as decision making processes become more participatory and transparent. In addition, this new reality of complex federal structures also requires that power inequities between entities, are openly acknowledged and managed. Despite these challenges, this is a non-negotiable journey for many international NGOs and they acknowledge the need to adapt their management mechanisms to better handle this internal complexity. First-hand experience sparked the interest to apply operational research and system dynamics approaches to one such management mechanism, that of resource planning and allocation within international NGOs. This study aims to develop a set of insights, based on the system dynamics model, that could be useful to international NGO decision makers as they respond to their “real life” resource allocation challenges. Problem structuring methods are applied to these resource allocation challenges to gain a deeper understanding of the core components of resource allocation in order to develop a generic system dynamics model that simulates the necessary behaviours based on stakeholder input. A set of management scenarios are developed and form the basis for conducting experimental runs on the generic system dynamics model, testing different parameters in an effort to compare quantitative results. These quantitative results are used to compare performance against the original generic model, analysing trends and model behaviour to inform qualitative recommendations and conclusions.